The Dynamics of Multiculturalism in Majelis Ta‟lim in an Najach Majelis Ta‟lim of Magelang - Huda, Imamul; Prastyo, Heru; Musa Asy‟arie,; Ayu Aryani, Sekar; Sumardjoko, Bambang (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to identify the lecture material in An Najach Majelis Ta'lim Magelang, Indonesia, from multicultural, anti-multicultural, and intolerance aspects. It also describes the impact of controversial lecture material which contains anti-multicultural and intolerance aspects. This study uses qualitative research methods and content analysis. Data collection methods are done through observation, interviews, and documentation. Results of this study: The topic of the public lecture is normative, emphasizing individual piety and multicultural values. Beside multicultural values, the public lectures also convey a message of intolerance and values of anti-multicultural such as truth claims, bias/prejudice, stereotypes against other groups, stigma and judgment, arrogance group, and hatred speeches or the public lecture contains a hate message. Even though Majelis Ta'lim conveys a message of intolerance and anti-multicultural values, it does not emerge from the destructive, radical, and intolerant actions of the congregations. Intolerance in An Najach Majlis Ta’lim is the inability of the public lecturer to refrain from disliking others, interfering, and/or opposing the attitudes or others beliefs expressed in his public lecture, but not disturbing others. This attitude of intolerance is caused by fake-simplification or overgeneralized beliefs which include stereotypes against "humiliated external groups", deep disgusted attitudes or dislike towards the external groups; however, it does not take negative actions against external groups member, both interpersonal and in terms of social-political policy.